Replication Data for: Physiological traits associated with drought resistance in Andean and Mesoamerican genotypes of common bean (Phaseolus vulgaris L.) - Polanía Perdomo, José A.; Rao, Idupulapati M.; Cajiao V., César Hernando; Rivera Peña, Mariela; Raatz, Bodo; Beebe, Stephen E. (International Center for Tropical Agriculture, 2016)
Traits and genotypes related with drought resistance in Mesoamerican and Andean gene pool in common beans. Results showed that five Mesoamerican lines SEA 5, SEA 15, SER 22, SER 16, SER 8 and one Andean line SEQ1003 have superior resistance to drought. The superior performance of these lines under drought stress was associated with better canopy biomass at mid-pod filling that could be related to deeper root system and effective use of water, combined with efficient remobilization of photosynthates from vegetative structures to pod development (pod partitioning index, PPI) and grain filling (pod harvest index, PHI).